Pendampingan Penentuan Harga Pokok Produksi Dan Harga Jual Produk Olahan Ikan Desa Karanganyar Kecamatan Kalianget - Astri Furqani; Arief Hidayatullah Khamainy; Dina Kurniawati; Rusnani Rusnani (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2023)
In any business, whether it is a large-scale enterprise or a small and medium-sized business (MSME), it is essential to calculate the Cost of Production to determine the selling price accurately. The purpose of providing assistance in determining the cost of production and selling price to the entrepreneurs of processed fish products in Karang Anyar village is to increase their knowledge and improve the profits of the "krupuk bandeng" (processed milkfish crackers) business. These entrepreneurs face various challenges, such as limited supply of raw milkfish due to the timing of the harvest, as the fish breeding areas are located in salt fields. This situation affects their potential income negatively. So far, these entrepreneurs have been determining the cost of production using traditional methods, where they accumulate all the costs of purchasing raw materials without considering labor costs, or they estimate it as best as they can. Additionally, when setting the selling price, they merely follow the prevailing market prices. Through this assistance, they will acquire fundamental knowledge in determining the cost of production and selling price of their processed fish products, even during non-harvest seasons of milkfish.